PENINGKATAN NILAI KEPEDULIAN SOSIAL MELALUI MODIFIKASI MODEL PEMBELAJARAN KONSIDERASI PADA MAHASISWA TINGKAT I PROGRAM STUDI PGSD FKIP UNIVERSITAS NUSANTARA PGRI KEDIRI - Soenarko, Bambang; Mujiwati, Endang Sri (Universitas Nusantara PGRI Kediri, 2015)
Today, human values ranging ignored, beaten by the thought / action hedonistic and pragmatic, which allows the moral decadence. This condition is necessary steps revamping definitely educational value with an appropriate learning model. Model considerations (Sensitivity consideration models) or models' sensitivity attention